Whitney’s jets for Sobolev functions - Bojarski, B. (Ukrains’kyi Matematychnyi Zhurnal, 2007)
We present two fundamental facts of the jet theory for Sobolev spaces $W^{m, p}$. One of them is that the formal differentiation of $k$-jets theory is compatible with the pointwise definition of Sobolev $(m - 1)$-jetspaces on regular subsets of Euclidean spaces $R^n$. The second result describes the Sobolev embedding operator of Sobolev jet spaces increasing the order of integrability of Sobolev functions up to the critical Sobolev exponent.